2020
DOI: 10.1002/cpt.1765
|View full text |Cite
|
Sign up to set email alerts
|

Does Hepatic Impairment Affect the Exposure of Monoclonal Antibodies?

Abstract: Limited information is available regarding the effect of hepatic impairment (HI) on the pharmacokinetics of monoclonal antibodies (mAbs). The results of an earlier report based on therapeutic proteins, including mAbs, approved through the end of 2012 were inconclusive due to limited HI data available at that time. New HI data for mAbs or antibody-drug conjugates (ADCs; with a focus on the mAb component) available between 2013 and 2018 were evaluated. The investigation indicates there is almost no data for seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Antibody drugs have a long half-life because they can escape proteolysis by lysosomes through binding with neonatal Fc receptors (FcRn), an endogenous IgG recycling mechanism 24 , 25 . The increased endogenous IgG can result in competitive FcRn binding with therapeutic antibody drugs, increased clearance of the drug, and decreased exposure of the target 26 . Additionally, our data showed a reduction in the albumin-globulin ratio in the hepatic impairment group, and its influence on antibody drug clearance was expected.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody drugs have a long half-life because they can escape proteolysis by lysosomes through binding with neonatal Fc receptors (FcRn), an endogenous IgG recycling mechanism 24 , 25 . The increased endogenous IgG can result in competitive FcRn binding with therapeutic antibody drugs, increased clearance of the drug, and decreased exposure of the target 26 . Additionally, our data showed a reduction in the albumin-globulin ratio in the hepatic impairment group, and its influence on antibody drug clearance was expected.…”
Section: Discussionmentioning
confidence: 99%
“…ADC conjugate exposure was generally comparable between patients with hepatic impairment and normal hepatic function for most of the approved ADCs, except for brentuximab vedotin and T-DM1 (Table 2 ). For brentuximab vedotin, ADC conjugate exposure (i.e., AUC) decreased by 35% in lymphoma patients with moderate hepatic impairment, and there was only one patient each with mild or severe hepatic impairment [ 35 ]. For T-DM1, AUC of T-DM1 conjugate at Cycle 1 in patients with mild and moderate hepatic impairment were approximately 38% and 67% lower than that of patients with normal hepatic function, respectively [ 36 ].…”
Section: Organ Dysfunction Studiesmentioning
confidence: 99%
“…mAbs have been thought not to be affected by chronic hepatic impairment due to their alternative metabolism. However, in a review of the pharmacokinetics of mAbs in hepatic impairment considering the available data from drug licences, published studies and pharmacokinetic modelling, Sun et al [87] found a small amount of reduced drug exposure for some mAbs in patients with mild hepatic impairment, and a more significant reduction in exposure in moderate hepatic impairment. No specific data was found for tocilizumab and disease severity was not fully described, where we know that clearance of mAbs is higher in patients with more severe disease or lower albumin.…”
Section: Hepatic Recommendationsmentioning
confidence: 99%
“…As the drug label does not include patients with hepatic impairment, and no data have been reported for sarilumab in the review by Sun et al [87] of mAbs in hepatic impairment, It is unclear whether there could be an alteration in drug exposure in patients with significant hepatic impairment. As a result, it is difficult to make a dosage recommendation in this population.…”
Section: Hepatic Recommendationsmentioning
confidence: 99%